The Effect of Project-Based Learning and Self-Efficacy on Soft Skills in Multicamera Projects - Wardhana, Aditya Kusuma; Degeng, I Nyoman Sudana; Praherdhiono, Henry; Kuswandi, Dedi; Choirudin, Choirudin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The government focuses on the challenges senior vocational high schools (SMK) face in producing competent and employable graduates. Issues include a lack of curriculum alignment with industry demands, low absorption of graduates in the job market, and mismatched competencies with industry needs, leading to a lack of mental readiness for work among graduates. This research aims to test the soft skills abilities of students being taught with PjBL and conventional models with high and low self-efficacy and the interaction between learning models and self-efficacy towards students' soft skills abilities. This research uses a quasi-experimental design. The research subjects were class XI students at SMKN 1 Blitar. This study selected 33 students in the experimental class and 33 in the control class. Learning in the experimental and control classes was carried out in 6 meetings with multicamera material—analysis of relationship and interaction data between variables using the two-way ANOVA test. The research results show a difference in soft skills abilities among students taught with the PjBL model and what is taught conventionally soft skills in high and low self-efficacy, as well as an interaction between the PjBL model and self-efficacy toward soft skills abilities. The research limitation only supports soft skills learning outcomes.